Implementasi Manajemen Berbasis Mutu dalam Lembaga Pendidikan Islam - Toto Suryadi; Khusnul Asma (MASALIQ, 2025)
This study stems from the limited research on the implementation of Total Quality Management (TQM) in Islamic educational institutions at the district level, despite its significant impact on the competitiveness and relevance of Islamic education in responding to both local and global dynamics. The aim of this research is to descriptively analyze the planning, implementation, evaluation, and the supporting and inhibiting factors in the application of TQM. A qualitative approach was employed using a multi-case study design involving one Madrasah Aliyah and one modern pesantren, both selected purposively. Data were collected through in-depth interviews, participatory observation, and document analysis, and then thematically analyzed. The findings reveal that both institutions have implemented TQM principles with distinct approaches: the Madrasah Aliyah emphasizes compliance with the National Education Standards (SNP) integrated with Islamic values, while the pesantren fosters a holistic quality environment covering academic performance, student self-reliance, mastery of classical Islamic texts (kitab kuning), and foreign languages. Key supporting factors include visionary leadership, an adaptive organizational culture, and active teacher involvement. Conversely, the main challenges lie in budget constraints, resistance to change, and difficulties in assessing non-academic quality indicators. The study concludes that synergy between the institutions' internal values and external demands is essential for effective TQM implementation. The implications highlight the need to strengthen evaluation systems and provide contextual, sustainable training for human resources to drive holistic quality improvement.